Simple, convenient, and nondestructive electromagnetic characterization technique for composite and multiscale hybrid samples at microwave frequencies. Issue 2 (February 2014) - Molenberg, Isabel; Bernal, Maria M.; Bollen, Pierre; Spote, David; Verdejo, Raquel; Pardoen, Thomas; Bailly, Christian; Huynen, Isabelle
ABSTRACT A new method is presented to characterize absorbing materials, based on a classical Line‐Line method but more nondestructive and more convenient. This modified Line‐Line technique is used to characterize polymer/carbon nanotubes composite foams. The advantages and limitations of this technique are highlighted and compared to those of the standard method. An advantageous use of the modified Line‐Line method in the particular case of multiscale hybrid materials is also presented and discussed. Finally, some conclusions are drawn. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:504–509, 2014